Integrating E-books into Science Teaching by Preservice Elementary School Teachers - Ching-san Lai (Journal of Education in Science, Environment and Health)
This study aims to discuss the issues of integrating e-books into science teaching by preservice elementary school teachers.  The study adopts both qualitative and quantitative research methods.  In total, 24 preservice elementary school teachers participated in this study.  The main sources of research data included e-books produced by preservice elementary school teachers, a feedback questionnaire on e-book production, and elementary school students’ feedback on the use of e-books.  The main results of the study are: (1) the preservice elementary school teachers were satisfied with the processes of e-book production; (2) the preservice elementary school teachers demonstrated excellent performance in e-book production; (3) elementary school students were happy to use e-books.